The Cellular Mitochondrial Genome Landscape in Disease. Issue 3 (March 2019) - Hahn, Anne; Zuryn, Steven
Abstract : Mitochondrial genome (mitochondrial DNA, mtDNA) lesions that unbalance bioenergetic and oxidative outputs are an important cause of human disease. A major impediment in our understanding of the pathophysiology of mitochondrial disorders is the complexity with which mtDNA mutations are spatiotemporally distributed and managed within individual cells, tissues, and organs. Unlike the comparatively static nuclear genome, accumulating evidence highlights the variability, dynamism, and modifiability of the mtDNA nucleotide sequence between individual cells over time. In this review, we summarize and discuss the impact of mtDNA defects on disease within the context of a mosaic and shifting mutational landscape. Highlights: Mutations of almost every mtDNA-encoded gene have been implicated in enhanced reactive oxygen species (ROS) production and disease. The spatiotemporal distribution of somatic mtDNA mutations within an individual is determined by their inheritance, formation, intercellular transfer, propagation, and removal over time. Diversity in the distribution and relative levels of mtDNA mutations (heteroplasmy) may contribute to varying rates of progression of aging and disease between cells of an individual. MtDNA heteroplasmy is modulated by stochastic and deterministic processes, including through the action of conserved homeostatic cellular mechanisms, such as fission/fusion, mitophagy, and the mitochondrial unfolded protein response.